1992
DOI: 10.1099/00221287-138-10-2051
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium in adhesion and germination of zoospore cysts of Pythium: a model to explain infection of host plants

Abstract: Newly-formed zoospore cysts of Pythiurn aphaniderrnaturn adhered to glass and germinated without a further trigger, but both adhesion and germination were suppressed by EGTA. Older (10 min) cysts adhered and germinated poorly unless supplied with Ca2+. Adhesion and germination were linked but separable, because young cysts germinated when dislodged from glass after 10 min, and older cysts kept in suspension germinated in response to high (7-10 mM) concentrations of Ca2+, Mg2+ or Sr2+. Other cations (Li+, Na+, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 29 publications
(20 reference statements)
0
35
0
2
Order By: Relevance
“…We also wanted to evaluate if the root damage was related to the crown defoliation and mineral nutrition of the trees, and thereby elucidate whether this pathogen may contribute to oak decline in southern Sweden. Since acidificationinduced nutrient imbalances of trees have been discussed as a cause for tree decline in Sweden, and the asexual as well as sexual reproduction of Phytophthora species are known to be influenced by soil chemistry [12,14,16,38,54], we also wanted to investigate if the root damage caused by P. quercina was related to the chemical conditions in the soil surrounding the tree. A field study, comparing the root systems, the tree nutrient status and the soil chemistry between healthy, moderately declining and severely declining oak trees in five stands with P. quercina was thus conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also wanted to evaluate if the root damage was related to the crown defoliation and mineral nutrition of the trees, and thereby elucidate whether this pathogen may contribute to oak decline in southern Sweden. Since acidificationinduced nutrient imbalances of trees have been discussed as a cause for tree decline in Sweden, and the asexual as well as sexual reproduction of Phytophthora species are known to be influenced by soil chemistry [12,14,16,38,54], we also wanted to investigate if the root damage caused by P. quercina was related to the chemical conditions in the soil surrounding the tree. A field study, comparing the root systems, the tree nutrient status and the soil chemistry between healthy, moderately declining and severely declining oak trees in five stands with P. quercina was thus conducted.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that these correlations are the result of an impeded water and nutrient uptake as a consequence of root damage caused by the pathogens. However, Phytophthora species are highly sensitive to environmental conditions, such as water availability [16], temperature [16] and soil chemistry [12,14,16,38,45,54]. In addition, various environmental factors may also affect the susceptibility of the trees to infection [19,34].…”
Section: Introductionmentioning
confidence: 99%
“…The most important reason for this is probably that zoospore encystment and cyst germination are influenced more by Ca 2ϩ fluxes and/or host surface compounds than by host exudates (11). Zoospores and cysts do not take up amino acids or glucose until germination (41), and the effects of these compounds on zoospores and cysts are hypothesized to be indirect by facilitating Ca 2ϩ channeling across the membranes (11,13). Because the role of sugars and amino acids in zoospore encystment and germination is probably secondary, bacterial competition for these compounds in exudates probably cannot result in large effects on these events.…”
mentioning
confidence: 99%
“…Two factors appeared to control the initial stages of invasion by Rozella: a soluble exudate which attracts Rozella zoospores, and a receptor on the cell wall surface which causes Rozella zoospores to adhere. Research on other zoosporic plant pathogens (Pythium and Phytophthora) suggested that zoospore adhesion and germination is regulated at a biochemical level by Ca 2+ and amino acids (Donaldson & Deacon 1992). The hypothesis that optimal biochemical rather than strictly environmental conditions must exist to cause an epidemic was not investigated in the present study, but warrants further investigation.…”
Section: Discussionmentioning
confidence: 74%